Reading Literacy, Mathematical Literacy, and Self-Confidence of Junior High School Students in Singkawang - Nurul Husna; Zulfahita Zulfahita; Sri Mulyani; Md. Shahinoor Rahman (STKIP Singkawang, 2020)
Literacy skills are very important abilities for students and are being encouraged to do so as a necessary prerequisite for lifelong learning. Because literacy skills are abilities that can be used to empower and improve the quality of individuals, families, communities, and countries. This study aims to (1) describe students' reading literacy and mathematical literacy skills based on the level of self-confidence of students in schools accredited A and B, as well as male and female students; (2) to test the comparability of reading literacy, mathematical literacy, and self-confidence based on the level of school accreditation and gender. The research method used in this research is descriptive quantitative. The sample in this study was selected using cluster sampling. The sample consisted of two public schools accredited A and B, and two private schools accredited A and B. The instruments in this study were reading literacy questions, mathematical literacy questions, student self-confidence questionnaires, and interview guidelines. The conclusions in this research are: (1) the descriptions are: (a) For schools with A accreditation, only confident students can process gathering information, processing information, and communicating information on reading literacy, while for mathematical literacy students who are confident can carry out the process Devising Strategies for Solving Problems indicators. For schools with B accreditation, students who are confident, confident enough, and less confident have carried out all the reading literacy processes, but there are still some mistakes and not according to the concept, while for mathematical literacy, students who are confident and confident enough can carry out process indicator Devising Strategies for Solving Problems. (b) For male students and female students who are confident, confident enough, and less confident to carry out the process of gathering information, processing information, and communicating information on reading literacy but still make some mistakes and do not fit the concept. As for mathematical literacy, confident female students can carry out the Communication process and Devising Strategies for Solving Problems. (2) For the comparison test, namely: (a) There is no difference in reading literacy between students from A and B accredited schools; (b) There are differences in mathematical literacy between students from A and B accredited schools; (c) There are differences in reading literacy and mathematical literacy between male students and female students; (d) There is no level of student confidence based on school accreditation and gender.